Impact of Political Institution Role to Anti-Corruption Perception Index: An Experience From Indonesia - Muhamad Ferdy Firmansyah (Training & Research Institute - Jeramba Ilmu Sukses, 2021)
Indonesian democracy from every period of government will continue to experience development towards maturity. In the life of the state, corruption cannot be separated. The role of political institutions and democratic maturity is very large in eradicating corruption, collusion and nepotism. This study uses secondary data, with used the Indonesian Democracy Index (IDI) and the Anti-Corruption Perspectives Index (Indeks Persepsi Anti-Korupsi/IPEK) which is sourced from the Indonesian Central Statistics Agency. Data processing using multiple linear regression statistical analysis. The Indonesian Democracy Index consists of variables of the role of the DPRD, the role of political parties, the role of the local government bureaucracy and the role of an independent judiciary. It was found that the role of DPRD has a significant positive effect on IPAK, the role of political parties has a significant negative effect on IPAK, the role of local government bureaucracy is significant positive and the role of an independent court is not significantly negative for IPAK. It is hoped that to improve the social community that is aware on anti-corruption, it is necessary to increase the role of the DPRD and the role of the local government bureaucracy in accordance with their duties and functions in the government together to eradicate corruption and form a new culture oriented towards the prevention and eradication of corruption.